Saisir les opportunités de ses vulnérabilités ? Trajectoire territoriale d’une station de moyenne montagne, Céüze 2000 - Anouk Bonnemains; Cécilia Claeys (Revue de Géographie Alpine)
This article analyses the territorial trajectory of Céüze 2000, one of the oldest ski resorts in the Hautes-Alpes, in an attempt to respond to the following question: to what extent do yesterday’s socio-economic vulnerabilities, worsened by today’s climate change, make Céüze 2000 a territory capable of serving as a laboratory for transition? Drawing on archival data, qualitative and quantitative field surveys, and a chrono-systemic timeline, the article underscores that yesterday’s development in Céüze 2000 may well become assets in today’s changing climate. Céüze 2000, which has not undergone major development plans or tourism improvements, has remained a social and local resort. Rather than transform it into a ghost resort, the closing of its ski lifts changed it into a space allowing individuals to embrace different forms of “slow sports”. The challenge in the coming years will be to promote these spontaneous uses, the success of which will depend on how well local actors can implement a coordinated territorial project.